2017
DOI: 10.1002/2017jb014423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a West Antarctic mantle plume on ice sheet basal conditions

Abstract: The possibility that a deep mantle plume manifests Pliocene and Quaternary volcanism and potential elevated heat flux in West Antarctica has been studied for more than 30 years. Recent seismic images support the plume hypothesis as the cause of Marie Byrd Land (MBL) volcanism and geophysical structure. Mantle plumes may more than double the geothermal heat flux above nominal continental values. A dearth of in situ ice sheet basal data exists that samples the heat flux. Consequently, we examine a realistic dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 140 publications
2
71
3
Order By: Relevance
“…Small amounts of partial melt, associated with the MBL volcanic systems, may also contribute to the seismic anomaly. The seismic signature is consistent with other studies suggesting a weak mantle plume, causing the MBL thermal anomalies and volcanism (e.g., Accardo et al, ; Seroussi et al, ), in that the velocity anomalies near the center of the dome are stronger and extend deeper than surrounding areas. At greater depth (>200 km), body wave tomography (i.e., Emry et al, ; Hansen et al, ) provides better images of this region, which suggests the presence of a possibly secondary plume structure.…”
Section: Discussionsupporting
confidence: 91%
“…Small amounts of partial melt, associated with the MBL volcanic systems, may also contribute to the seismic anomaly. The seismic signature is consistent with other studies suggesting a weak mantle plume, causing the MBL thermal anomalies and volcanism (e.g., Accardo et al, ; Seroussi et al, ), in that the velocity anomalies near the center of the dome are stronger and extend deeper than surrounding areas. At greater depth (>200 km), body wave tomography (i.e., Emry et al, ; Hansen et al, ) provides better images of this region, which suggests the presence of a possibly secondary plume structure.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, there is no evidence from the An model that there are any regions of high Antarctic heat flow corresponding to the elevated values of northern India, yet the Martos model shows a circular feature of high heat flow at this location. Elevated heat flow at the southern edge of George V Land is imaged in all geophysical models and is a result of the West Antarctic Rift System, driven by recent magmatism and the likely presence of a magmatic plume (Ivins et al, ; Seroussi, Ivins et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Zones of elevated GHF below the WAIS can produce considerable volumes of subglacial meltwater (Vogel & Tulaczyk, ) and may contribute to the development and dynamics of subglacial lakes, the advection of organic and inorganic compounds into subglacial habitats, and thus the presence and metabolism of microbial biomes (Christner et al, ; Jørgensen & Boetius, ). Seroussi et al () found that locally high GHF (≥150 mW m −2 ) below the Whillans Ice Stream was needed to reproduce the observed subglacial lakes in an ice sheet model. As the ice sheet thins, increasing the vertical conductive heat flux, GHF variability may be more important to predictions of the basal thermal regime, particularly the development of basal frozen zones such as ice rises that might stabilize ice retreat (Favier & Pattyn, ; Rignot et al, ).…”
Section: Discussionmentioning
confidence: 99%